Porous cationic polymers: the impact of counteranions and charges on CO2 capture and conversion. Issue 5 (19th November 2015) - Buyukcakir, Onur; Je, Sang Hyun; Choi, Dong Shin; Talapaneni, Siddulu Naiudu; Seo, Yongbeom; Jung, Yousung; Polychronopoulou, Kyriaki; Coskun, Ali
Abstract : Porous cationic polymers (PCPs) with surface areas up to 755 m 2 g −1 bearing positively charged viologen units in their backbones and different counteranions have been prepared. Abstract : Porous cationic polymers (PCPs) with surface areas up to 755 m 2 g −1 bearing positively charged viologen units in their backbones and different counteranions have been prepared. We have demonstrated that by simply varying counteranions both gas sorption and catalytic properties of PCPs can be tuned for metal-free capture and conversion of CO2 into value-added products such as cyclic carbonates with excellent yields.